Alkaloids - Alternatives in Synthesis, Modification and Application 2017
DOI: 10.5772/intechopen.69847
|View full text |Cite
|
Sign up to set email alerts
|

The Local Anesthetic and Pain Relief Activity of Alkaloids

Abstract: Alkaloids have been known for several centuries and have been mainly obtained from natural sources that presented important properties with biochemical, pharmacological, and medical effects in living organisms. Alkaloids are derived from amino acids like other important molecules in the functioning of life in our body. Hence, alkaloids are considered as pharmacologically important. Alkaloids are secondary metabolites widely distributed in leaves, stem, root, and fruits of plants which synthesize them. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…Thus, alkaloids such as berberine show antibacterial activity on A. actinomycetemcomitans and P. gingivalis species, and it is observed that the mechanism of action consist in inhibition of collagenase enzyme activity [33]. Additionally, alkaloids find their practical utility in dentistry as local anesthetics, being used in various dental interventions [34]. These compounds also have a beneficial effect in viral infections due to their ability to stimulate the host's immune system by increasing interferon synthesis and stimulating macrophage activity.…”
Section: Vegetal Sources Of Compounds On Dentistry Productsmentioning
confidence: 99%
“…Thus, alkaloids such as berberine show antibacterial activity on A. actinomycetemcomitans and P. gingivalis species, and it is observed that the mechanism of action consist in inhibition of collagenase enzyme activity [33]. Additionally, alkaloids find their practical utility in dentistry as local anesthetics, being used in various dental interventions [34]. These compounds also have a beneficial effect in viral infections due to their ability to stimulate the host's immune system by increasing interferon synthesis and stimulating macrophage activity.…”
Section: Vegetal Sources Of Compounds On Dentistry Productsmentioning
confidence: 99%
“…Alkaloids are secondary metabolites, broadly spread in a different part of plants such as leaves, stem, root, fruits, etc.. [1] They have exhibited significant biological activities in living organisms such as anticholinesterase action, [2] antioxidant, [3] anxiolytic, [4] antimicrobial, [5] anti-HIV, [6] antiparastic, [7] antiinflammatory [8] and antidepressant. [9] Despite the extensive research and work on the extraction, separation and purification of several alkaloids, due to their intricate structures and tedious processes, only a small number of them could be provided from natural sources in commercial amounts.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Despite the extensive research and work on the extraction, separation and purification of several alkaloids, due to their intricate structures and tedious processes, only a small number of them could be provided from natural sources in commercial amounts. [1] Thus, the improvements of various effective and useful protocols for their total syntheses have still encouraged several research groups, worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Drugs containing an amino group are key pharmaceutical agents, covering a broad spectrum of biological actions and displaying anti-inflammatory [ 1 ], anticancer [ 2 , 3 ], antimicrobial [ 4 , 5 ], and pain-relieving properties [ 6 ]. Currently, 542 drugs containing an amino group have already been approved for the EU market, according to the drug bank online ( , accessed on 15 July 2021).…”
Section: Introductionmentioning
confidence: 99%